Immunogenicity of Infliximab Among Patients With Behçet Syndrome: A Controlled Study - Esatoglu, Sinem Nihal; Akkoc-Mustafayev, Fatma Nihan; Ozguler, Yesim; Ozbakır, Fatma; Nohut, Okan K.; Cevirgen, Dilsen; Hamuryudan, Vedat; Hatemi, Ibrahim; Celik, Aykut Ferhat; Yazici, Hasan; Hatemi, Gulen (Frontiers in Immunology, 2020)
Background: Immunogenicity of tumor necrosis factor alpha inhibitors (TNFis) has been recognized as an important problem that may cause loss of efficacy and adverse events such as infusion reactions. TNFis are being increasingly used among patients with Behçet’s syndrome (BS) and scarce data exist on this topic. Objective: We aimed to investigate the prevalence of anti-infliximab (IFX) antibodies in patients with Behçet syndrome together with suitable controls. Methods: We collected serum samples from 66 consecutive Behçet syndrome patients (51 M, 15 F, mean age 37±9 years) who were treated with IFX. Additionally, similarly treated 27 rheumatoid arthritis, 53 ankylosing spondylitis, 25 Crohn’s disease patients, and 31 healthy subjects were included as controls. Samples were collected just before an infusion, stored at -80oC until analysis, and serum IFX trough levels and anti-IFX antibodies were measured by ELISA. We used a cut-off value of 1 μg/mL for serum IFX trough level, extrapolating from rheumatoid arthritis studies. Results: Anti-IFX antibodies were detected in 4 (6%) Behçet syndrome, 5 (18.5%) rheumatoid arthritis, 3 (12%) Crohn’s disease, and 1 (2%) ankylosing spondylitis patient. The median serum IFX trough level was significantly lower in patients with anti-IFX antibodies compared to those without antibodies (2.32 (IQR: 0.6-3.6) vs 3.35 (IQR: 1.63-5.6); p=0.019). The serum IFX trough level was lower than the cut-off value in 6/13 (46%) patients with anti-IFX antibodies and in 25/158 (16%) patients without anti-IFX antibodies (p=0.015). Among the 4 Behçet syndrome patients with anti-IFX antibodies, 2 experienced relapses and 2 had infusion reactions. Conclusions: Immunogenicity does not seem to be a frequent problem in Behçet syndrome patients treated with IFX, but may be associated with relapses and infusion reactions, when present.